2016
DOI: 10.31018/jans.v8i1.802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungal pathogens, Fusarium semitectum Berk. and Ravenel and Hirsutella thompsonii Fisher against red spider mite, Tetranychus neocaledoni-cus (Andre) of okra under laboratory and greenhouse conditions

Abstract: Efficacy of fungal pathogens, Fusarium semitectum Berk. and Ravenel and Hirsutella thompsonii Fisher was evaluated against red spider mite, Tetranychus neocaledonicus (Andre) of okra under laboratory and greenhouse conditions. Among the treatments evaluated under laboratory conditions, the highest mortality of 78.20 and 88.34 percent adults and immatures, respectively was recorded at 2.10 x 109 spores per ml of F. semitectum, whereas it was 82.05 and 92.31 per cent adults and immatures, respectively in case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The results showed that all stages were susceptible to both H. thompsonii was more effective against eggs at its LC 50 value. Similar results were obtained by Fiedler et al [27], Tamai et al [25], and Rachana et al [24] during their studies on mites [28].…”
Section: Virulence Of Entomopathogenic Fungal Isolatessupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that all stages were susceptible to both H. thompsonii was more effective against eggs at its LC 50 value. Similar results were obtained by Fiedler et al [27], Tamai et al [25], and Rachana et al [24] during their studies on mites [28].…”
Section: Virulence Of Entomopathogenic Fungal Isolatessupporting
confidence: 90%
“…The host preference of the isolates might vary based on the species, or it could be attributed to differences in the production of extracellular enzymes [21,23]. Rachana et al [24] reported that the treatment with H. thompsonii at 4.6x10 2). The results of lethal time (50 and 90 percent mortality) showed that the LT 50 and LT 90 values for Isaria isolate were higher (6.19 days and 11.03 days, respectively) compared with Hirsutella isolate (5.99 days and 11.12 days, respectively) (Table 3).…”
Section: Virulence Of Entomopathogenic Fungal Isolatesmentioning
confidence: 99%
“…as efficient entomopathogen against many insects including Culex quinquefsciatus, Anopheles stephensi, Sitophilus oryzae, Tetranychus neocaledonicus, Tropidacris collaris, Lymantria obfuscate, Tetranychus urticae etc. (Munshi et al, 2008;Mohanty et al, 2008;Rachana et al, 2009;Pelizza et al, 2011;Batta, 2012;Tangtrakulwanich et al, 2014;Vivekanandhan et al, 2018;Wu et al, 2018). Santos et al (2020) published a review study based on a survey of peer-reviewed papers published from 2000 to 2019, presenting the significant pathogenicity of Fusarium spp.…”
Section: Entomopathogenic Efficacy Of Locally Isolated Fusarium Sppmentioning
confidence: 99%